2018
DOI: 10.1093/inthealth/ihy004
|View full text |Cite
|
Sign up to set email alerts
|

Donation programme of returned medicines: role of donors and point of view of beneficiaries

Abstract: The donations covered about one-third of the volume of medicines used by beneficiary organizations. The programme helped to decrease expenditure by both patients and health facilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…A small pilot in Singapore has also identified the huge potential for medicines reuse to reduce medication wastage and costs [ 18 ]. Researchers examining the benefit of long-term donation programmes in Europe, Africa and Latin America, against WHO’s formal advice to withhold such donations, also report a decrease in expenditure by both patients and health facilities [ 19 ]. The issue of lack of accountability for the over-ordering of medicines identified by our stakeholders associated with free prescriptions has also been debated before, with one suggestion being to charge a nominal £1 fee for prescription items to create a symbolic contract for patients to take their medicines more responsibly [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…A small pilot in Singapore has also identified the huge potential for medicines reuse to reduce medication wastage and costs [ 18 ]. Researchers examining the benefit of long-term donation programmes in Europe, Africa and Latin America, against WHO’s formal advice to withhold such donations, also report a decrease in expenditure by both patients and health facilities [ 19 ]. The issue of lack of accountability for the over-ordering of medicines identified by our stakeholders associated with free prescriptions has also been debated before, with one suggestion being to charge a nominal £1 fee for prescription items to create a symbolic contract for patients to take their medicines more responsibly [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Humanitarian causes (wars, epidemics) are the pivotal reasons behind donations (Collins, 2004;Colatrella, 2008). One of the main criticism of medicines donations is the mismatch between what poor communities need and what is given (Jenny et al, 2016;Guilbaud, 2018;Nicoli et al, 2018). A typical example of negative results associated with medicines donations is the case of the Bosnia and Herzegovina war (1992-96), during which around 60% of the given medicines were misappropriated (Beckmans et al, 1997).…”
Section: Eou-m Donation Programsmentioning
confidence: 99%
“…-In what stages of the PSC donations occur It is difficult to precisely identify in what part of the PSC donations take place. Reviewed studies (see Appendix E) indicate that it happens between diverse sources and end users (Bero et al, 2010;Nicoli et al, 2018). From the reading of the selected papers, a depiction is provided in Figure 7, in order to indicate answers to this question <Fig 7 here> -Recommendations for improving EOU-M donations The review found that collaboration between stakeholders (Kale et al, 2013;Guilbaud, 2018) and adherence to best practices guidelines (Beckmans et al, 1997) are the core suggestions for improving EOU-M donations.…”
Section: Eou-m Donation Programsmentioning
confidence: 99%
See 1 more Smart Citation
“…Canadian doctors, for example, have called for the recycling of expensive cancer drugs for disadvantaged patients [ 6 ], and in the UK in 2012, even the then director of the NHS Sustainable Development Unit argued for research-informed debate on medicines reuse [ 7 ]. Indian academics have called for medicines reuse to be explored [ 8 ], and researchers from Italy have examined the pros and cons of donating returned medicines to organizations in Europe, Africa and Latin America against WHO’s formal advice to withhold such donations [ 9 ]. However, it is also worth noting that research shows that underground medication exchange activities are already taking place among patients, for example with diabetes medication [ 10 ], which negates these “intellectual” arguments about medicines reuse.…”
Section: Introductionmentioning
confidence: 99%